In Vitro Antimicrobial Photodynamic Therapy for Pseudomonas aeruginosa (P. aeruginosa) and methicillin-resistant Staphylococcus aureus (MRSA) Inhibition Using a Green Light Source - Karen Roa-Tort; Yael Saavedra; Angélica Villanueva-Martínez; Adriana Ganem-Rondero; Laura Abril Pérez-Carranza; José M. de la Rosa-Vázquez; Gabriel Ugalde-Femat; Omar Molina-Alejandre; Andrea Angela Becerril-Osnaya; Josué D. Rivera-Fernández (MDPI AG, 2024)
Photodynamic therapy (PDT) has been based on using photosensitizers (PS) and applying light of a specific wavelength. When this technique is used for treating infections, it is known as antimicrobial photodynamic therapy (aPDT). Currently, the use of lighting sources for in vitro studies using aPDT is generally applied in multiwell cell culture plates; however, depending on the lighting arrangement, there are usually errors in the application of the technique because the light from a well can affect the neighboring wells or it may be that not all the wells are used in the same experiment. In addition, one must be awarded high irradiance values, which can cause unwanted photothermal problems in the studies. Thus, this manuscript presents an in vitro antimicrobial photodynamic therapy for a Pseudomonas aeruginosa (P. aeruginosa) and methicillin-resistant Staphylococcus aureus (MRSA) inhibition study using an arrangement of thermally isolated and independently illuminated green light source systems for eight tubes in vitro aPDT, determining the effect of the following factors: (i) irradiance level, (ii) exposure time, and (iii) Rose Bengal (RB) concentration (used as a PS), registering the Pseudomonas aeruginosa (P. aeruginosa) and methicillin-resistant Staphylococcus aureus (MRSA) inhibition rates. The results show that in the dark, RB had a poor antimicrobial rate for P. aeruginosa, finding the maximum inhibition (2.7%) at 30 min with an RB concentration of 3 µg/mL. However, by applying light in a correct dosage (time × irradiance) and the adequate RB concentration, the inhibition rate increased by over 37%. In the case of MRSA, there was no significant inhibition with RB in complete darkness and, in contrast, the rate was 100% for those experiments that were irradiated.